Analytical Study of Combined Convection Heat Transfer for Flow in a Horizontal Annulus (University of Thi-Qar Journal for Engineering Sciences, 2011)
In this paper a numerical investigation is made to study the axially symmetric, laminar air flow in the entrance region of an annulus by solving the two dimensional governing equations of motion ( continuity, momentum & energy ) using implicit finite difference method and the Gauss elimination technique. A STAR CCM + program is used. The results obtained for velocity and temperature profile revealed that, the secondary flow created by natural convection have a significant effect on the heat transfer process. A comparison has been made for results which show a good agreement.